Multimodalni logistični center Novo Mesto v fokusu gospodarskega razvoja jugovzhodne Slovenije - Murtič, Sašo (Perfectus AC, 2018)
In the field of global economic development, a developmental revolution has taken place over the last thirty years, bringing together global industry, the global market, and the large international corporations that control the entire economy. The market offered new products, improved and modernized technique and technology, and at the same time new and previously unknown products appeared on the market, attracting many customers and changing rigid production processes and processes that support production. New products have changed the form of communication, networking, data transfer and e-commerce. New shifts have been made in the field of economic inter-organizational integration and in the field of media technology and digitalization of economic processes (Davidović, 2000). At the same time, great scientific steps were taken in the field of the automotive industry, which enabled the introduction of autonomous devices and robots into production, thus beginning the search for human-machine cooperation. The industry designed and engineered new and more modern motor vehicles, the development of modern electric vehicles began, which was also joined by Revoz d.d. Novo mesto. In the field of infrastructure, new and high-speed rail links have been built, which have become cost-effective and friendly, and low-cost transport between continents has emerged in the airspace, enabling the rapid movement of goods and the travel of people, even those not previously could afford. There has been a rapid economic development of China, India and other parts of the Eastern world, where new markets have opened up for European and American manufacturers. There was a great expansion of products between continents, followed by trade in goods between Europe, Asia, America and other continents. There have also been changes in the field of sustainable development, protection of the environment and nature, population migration and general intercultural expansion. Science attributes rapid and demanding changes to the globalized development of the economy, the general globalization of production and the market, logistics and logistics processes that are conditioned by change. It changed the course and development of the world in many ways, caused many shifts in terms of market expansion and intercontinental integration, and at the same time had a strong impact on the development of new infrastructure, transport and logistics. During this development period of Industry 4.0, a relatively new container intercontinental transport emerged, which was already known to be so useful, but required the development of ports in coastal and river places. As a result, large multimodal logistics centres were developed, which received goods and carried out logistics processes for the customer. Countries began connecting railroads and roads to seaports and river ports, and built airports in the immediate vicinity. There was an approximation of existing infrastructures to a connection point, which allowed fast transhipment or loading of goods for further transport. As part of this development, through relevant and verified data, we looked for opportunities for the location of multimodal logistics centres in Slovenia and their connection with the world in the region and outside the Republic of Slovenia. Through the methodology of the study, we defined Novo mesto and the surroundings of south-eastern Slovenia as the most economically developed region in the country and hypothesized that a modern logistics centre could be placed in its space, which would play an important role in the implementation of logistics and logistics processes and South-Eastern Europe.
Keywords: containerization; digitalizacija; digitalization; infrastructure; infrastruktura; kontejnerizacija; logistics; logistics platform; logistics processes; logistična platforma; logistični procesi; logistika; multimodal logistics centre; multimodalni logistični center